Correlations between gastrointestinal and oral microbiota in children with cerebral palsy and epilepsy - Huang, Congfu; Chu, Chunuo; Peng, Yuanping; Zhang, Nong; Yang, Zhenyu; You, Jia; Wei, Fengxiang (Frontiers in Pediatrics, 2022)
To study the correlation between gut and oral microbiota for children with cerebral palsy and epilepsy. In this study, we enrolled twenty-seven children with cerebral palsy and epilepsy (CPE) from the social welfare center of Longgang District, collected their oral plaque and stool samples, and analyzed the gut microbiota (GM) and oral microbiota (OM) with 16S rRNA sequencing. With taxonomical annotation, we discovered that the levels of Firmicutes and Bacteroides in the oral cavity were significantly lower in the CPE children than those in healthy children, and the abundance of Actinomycetes increased significantly in CPE children conversely. In addition, Prevotella, Fusobacterium, and Neisseria were the top three abundant genera in the OM, representing 15.49%, 9.34%, and 7.68% of the OM and suggesting potential correlations with caries and periodontitis, and malnutrition. For the GM, Bifidobacterium, Bacteroides, and Prevotella were the top three abundant genera in the CPE children, and the bacteria probably contributed to the development of chronic inflammation and malnutrition. Furthermore, the OM and GM correlated with each other closely, and the bacterial components of the GM and OM in the CPE children differed from those in healthy children notably, such as Bifidobacterium, Fusobacterium, Bacteroides, and Neisseria. In conclusion, dysbiotic OM can translocate to the intestinal tract and induce GM dysbiosis, suggesting the consistency between oral microbiota and GM variations. Altered oral and gut microbial structures exhibited potential impacts on the occurrence of clinical diseases such as periodontitis, caries, and malnutrition.